Porphyromonas gingivalis outer membrane vesicles exacerbate retinal microvascular endothelial cell dysfunction in diabetic retinopathy - Huang, Shengyuan; Cao, Guoqin; Dai, Dong; Xu, Qiuping; Ruiz, Sunniva; Shindo, Satoru; Nakamura, Shin; Kawai, Toshihisa; Lin, Jiang; Han, Xiaozhe (Frontiers in Microbiology, 2023)
Diabetic retinopathy (DR) is one of the leading causes of blindness. Periodontitis is one of the highest oral incidences and has been closely related to various systemic conditions through Porphyromonas gingivalis. P.gingivalis OMVs, derived from Porphyromonas gingivalis, can cause endothelial dysfunction and potentially affect microvascular. Current epidemiological studies provide limited evidence suggesting that periodontitis is associated with DR. However, there is a lack of basic research elucidating how periodontitis affects the severity of DR. This study demonstrated that P.gingivalis OMVs induced damage to the blood-retinal barrier in mice. In vitro studies showed that the expression of inflammatory factors in human retinal microvascular endothelial cells (HRMECs) was increased after P.gingivalis OMVs stimulation. Increased reactive oxygen species, mitochondrial dysfunction, cell death, and altered endothelial permeability were observed. In addition, protease-activated receptor-2 (PAR-2) regulated OMVs-induced TNF-α, MMP-9 mRNA expression, cell death, and endothelial permeability. Overall, we suggested that P.gingivalis OMVs induced mitochondria-related cell death of HRMECs and accelerated endothelial dysfunction, thus aggravating DR, in which PAR-2 plays a potential role. This study is the first research report to delineate the potential molecular mechanism of P.gingivalis OMVs on DR pathogenesis, which uniquely focused on elucidating the possible impact of periodontal pathogen derivatives on DR progression.